ANALISIS DAN PERANCANGAN SISTEM INFORMASI AKUNTANSI PENJUALAN DAN PENERIMAAN KAS (ONLINE SHOP KANTONG ASI BAABAA BAGBIT) - wardani; Rika Yuliastuti; vica budi, Anggun (Ekomania, 2023)
The background of this research is that the sales system and cash receipts are a system that has a major influence on the success of a company because sales are the main activity carried out by companies to make profits while cash receipts are a benchmark for success in sales at a companyThe problem in this research is how to apply the sales accounting information system to the online Baabaa and Bagbit breast milk business and whether the control system over the sales and cash receipts in the online Baabaa and Bagbit breast milk business is adequate. This research is a descriptive research with a qualitative approach. The findings of this study are that the online business of Baabaa and Bagbit has implemented its accounting information system quite well. Documents used in the sales and cash receipts system in Baabaa and Bagbit breast milk bags include invoices and proof of payment. The accounting records used in the online business of Baabaa and Bagbit kantoang asi are cash receipts and cash disbursements which are still manual, which is still using records in books. The recommendation that can be given is that it is better to record transactions using a computer in order to minimize the possibility of errors when recording and make it easier when reporting sales information.